2018
DOI: 10.1016/j.egja.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Erector Spinae Block a safe, simple and effective analgesic technique for major hepatobiliary surgery with thrombocytopenia

Abstract: A B S T R A C THepatobiliary surgeries are associated with severe pain, and coagulopathy. Adequate pain control is vital and difficult to achieve for these patients. Epidural analgesia is considered the routine standard technique for the management of both somatic and visceral pain from major abdominal surgeries until now. However, it is invasive, blind and carries the risk of dural or vascular puncture. Coagulopathy found in patients posted for hepatobiliary surgery further increases the concerns. We found ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…In-hospital use has been described in coagulopathic patients without complications. 9,10 The underlying bony anatomy makes identification of the target area easy and protects underlying structures from damage should needle placement be off target. Reported complications include pneumothorax, 11 incomplete blockade, 12 and motor block.…”
Section: Discussionmentioning
confidence: 99%
“…In-hospital use has been described in coagulopathic patients without complications. 9,10 The underlying bony anatomy makes identification of the target area easy and protects underlying structures from damage should needle placement be off target. Reported complications include pneumothorax, 11 incomplete blockade, 12 and motor block.…”
Section: Discussionmentioning
confidence: 99%
“…Pain is caused by the sub-costal J-shaped incision, the retraction of ribs, and diaphragmatic irritation. Adequate analgesia is important since inadequate pain control can lead to an increased risk of atelectasis, respiratory failure, and prolonged stay in the hospital [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many recently published studies have reported the favourable effects of ESPB as postoperative analgesia in different types of surgery, such as breast surgery, abdominal surgery, thoracic surgery and hip reconstructions. However, few of these studies assessed the effect of ESPB as postoperative analgesia in spine surgery, and most of these studies were done on a small number of patients that were not fully blinded to the study [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%